A PHILOSOPHICAL ANALYSIS OF FREE WILL AND THE ILLUSION OF CHOICE UNDER THE CONDITIONS OF DIGITAL TRANSFORMATION (Eureka Journal of Humanities and Social Research, 2026)
This article subjects to philosophical analysis the problem of free will and the illusion of choice under the conditions of digital transformation. On the basis of an analysis of international scholarly sources from the period 2020–2025, the study examines the extent to which a person’s genuine freedom of will is preserved within the contemporary environment of algorithmic recommender systems, predictive artificial intelligence, and surveillance capitalism. The article comparatively engages R. Sapolsky’s position of hard determinism, Sh. Zuboff’s theory of “behavior modification,” M. Coeckelbergh’s notion of epistemic agency, and the compatibilist approach. The investigation advances “digital heteronomy” as a new philosophical concept: the situation in which the individual regards his or her own choice as free while it has, in fact, been shaped in advance by an algorithmic architecture.
Keywords: Free will, illusion of choice, digital transformation, surveillance capitalism, algorithmic curation, epistemic agency, predictive AI, determinism, compatibilism, digital heteronomy.